THU0164 Subclinical atherosclerosis and cardiovascular events in italian patients with rheumatoid arthritis: results from multicenter girrcs (gruppo italiano di ricerca in reumatologia clinica e sperimentale) study. (15th June 2017) - Ruscitti, P; Margiotta, DPE; Navarini, L; Macaluso, F; Iacono, D; D'Onofrio, F; Emmi, G; Atzeni, F; Prete, M; Perosa, F; Sarzi-Puttini, P; Emmi, L; et al.
Abstract : Background: Several studies showed a close relationship between Rheumatoid Arthritis (RA) and accelerated atherosclerosis [1, 2]. At the best of our knowledge, no such study has been carried out in a large Italian series. Objectives: To investigate the prevalence of presence of subclinical atherosclerosis and history of cardio-cerebrovascular events (CVEs), in 1266 patients consecutively admitted to Rheumatology Units throughout the whole Italy. Methods: From 01/01/2015 to 31/12/2015, 1266 consecutive patients admitted to GIRRCS centres, satisfying ACR/EULAR criteria for RA were investigated for: i. traditional cardiovascular risk factors: gender, age, smoking habit, cholesterol, triglycerides, glycemia, systemic arterial hypertension (SAH), metabolic syndrome (MS), type 2 diabetes (T2D); ii. RA aspects: disease duration as assessed from the first symptom, disease activity as evaluated by DAS28, radiographic damage by joint X-ray, and joint surgery; iii. subclinical atherosclerosis, as assessed by ultrasound technique and/or atherosclerotic peripheral lesions; iv. history of CVEs. Results: We evaluated 1176 patients out of 1266, that were investigated for both CVEs and subclinical atherosclerosis. They were mostly females (80.52%), with a median age of 60 years (range 18–91 years), a median disease duration of 12 years (range 0.8–25 years), seropositive in 69.21%. Nineteen percent were in remission; 17.51% presented low disease activity; 39.45% moderate disease activity, 22.61% high disease activity. Out of 1176 patients, 217 (18%) showed evidence of subclinical atherosclerosis: a figure lower than that reported worldwide (32.7%) [2]. Eighty-two patients (6.9%) had a history for CVEs (58 myocardial infarction, 38 heart failure, 10 ischemic transitory attack, 7 Stroke), too this figure is lower than that reported worldwide (8.5%) [3, 4]. In multivariate analysis, older age (p=0.0001, OR:1.069, CI95%:1.05–1.09), MS (p=0.0001, OR:3.417, CI95%:2.16–5.40) and SAH (p=0.0001, OR:3.714, CI95%:2.23–6.17) and high disease activity (p=0.001, OR:2.117, CI95%:1.35–3.32) were significantly associated with the presence of subclinical atherosclerosis. Male gender (p=0.0001, OR:3.465, CI95%:1.94–6.185), MS (p=0.005, OR:2.542, CI95%:1.29–4.52), T2D (p=0.007, OR:2.324, CI95%:1.29–4.29) and SAH (p=0.001, OR:4.921, CI95%:2.14–11.45) and higher disease activity (p=0.003, OR:1.316, CI95%:1.15–1.68) were significantly associated with a history of CVEs. Conclusions: This is the first Italian multicenter study on subclinical and clinical atherosclerosis in patients with RA. We pointed out a low prevalence of both subclinical atherosclerosis and history of CV events. Nonetheless, a high disease activity and presence of cardiovascular risk factors were found to play a role, similarly to other countries. References: Ruscitti P, et al. PLoS One. 2017;12:e0170108. Ambrosino P, et al. Thromb Haemost. 2015;113:916–30. Solomon D et al. Ann Rheum Dis. 2010;69:1920–5. Avina-Zubieta JA, et al. Ann Rheum Dis. 2012;71:1524–9. Disclosure of Interest: None declared